532 SEX-RELATED DIFFERENCES IN THROMBUS BURDEN IN ST-ELEVATION MYOCARDIAL INFARCTION PATIENTS UNDERGOING PRIMARY PERCUTANEOUS CORONARY INTERVENTION. (15th December 2022) - Manzi, Maria Virginia; Buccheri, Sergio; Jolly, Sanjit S; Zijlstra, Felix; Frobert, Ole; Lagerqvist, Bo; Mahmoud, Karim D; Dzavik, Vladimir; Barbato, Emanuele; Sarno, Giovanna; James, Stefan
Abstract: Background: Women have a worse prognosis after ST-segment elevation myocardial infarction (STEMI) than men. The prognostic role of thrombus burden (TB) in influencing the sex-related differences in clinical outcomes after STEMI has not been clearly investigated. Objectives: The aim of this study was to assess the sex-related differences in TB and its clinical implication in patients with STEMI. Methods: We analyzed individual patient data from the 3 major randomized clinical trials of manual thrombus aspiration, encompassing a total of 19, 047 patients with STEMI, of whom 13, 885 (76.1%) were men and 4, 371 (23.9%) were women. The primary outcome of interest was 1-year cardiovascular (CV) death. The secondary outcomes of interest were recurrent myocardial infarction, heart failure, all-cause mortality, stroke, stent thrombosis (ST), and target vessel revascularization at 1 year. Results: Patients with high TB (HTB) had worse 1-year outcomes compared with those presenting with low TB (adjusted HR for CV death; 1.52; 95% CI: 1.10-2.12; P=0.01). In unadjusted analyses, female sex was associated with an increased risk for 1-year CV death regardless of TB. After adjustment, this risk for 1-year CV death was higher only in women with HTB (HR 1.23, 95% CI: 1.18-1.28; P<0.001) who also had an increased risk for all-cause death and ST than men. Conclusion: In patients with STEMI, angiographic evidence of HTB negatively affected prognosis. Among patients with HTB, women had an excess risk for stent thrombosis, CV and all-cause mortality than men. Further investigations are warranted to better understand the pathophysiological mechanisms leading to excess mortality in women with STEMI and HTB.